Neutron/muon correlation functions to improve neutron detection capabilities outside nuclear facilities - Ordinario, Donald Thomas, author; Brandl, Alexander, advisor; Johnson, Thomas, committee member; Wilson, Robert, committee member (Colorado State University. Libraries, 2016)
The natural neutron background rate is largely due to cosmic ray interactions in the atmosphere and the subsequent neutron emission from the interaction products. The neutron background is part of a larger cosmic radiation shower that also includes electrons, gamma rays, and muons. Since neutrons interact much differently than muons in building materials, the muon and neutron fluence rates in the natural background can be compared to the measured muon and neutron fluence rate when shielded by common building materials. The simultaneous measurement of muon and neutron fluence rates might allow for an earlier identification of man-made neutron sources, such as hidden nuclear materials. This study compares natural background neutron rates to computer simulated neutron rates shielded by common structural and building materials. The characteristic differences between neutrons and muons resulted in different attenuation properties under the same shielded conditions. Correlation functions between cosmic ray generated neutrons and muons are then used to predict neutron fluence rates in different urban environments.